INTERPRETASI TIPOLOGI DESA RAMAH PEREMPUAN (Studi Kasus di Desa Cahaya Negeri, Kabupaten Seluma) - Zulhakim, Abdul Aziz (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to interpret the typology of Women-Friendly Villages through the fulfilment of SDGs indicator number 5 in Cahaya Negeri Village, Sukaraja Sub-district, Seluma District. The research method used was a descriptive qualitative approach, with data collection through in-depth interviews with key informants who have knowledge and experience as development actors in Cahaya Negeri Village, as well as review of relevant documents such as regulations and official documents. The data was analysed using a content analysis approach to identify the main themes, patterns and meanings that emerged from the collected data. The results explain that Cahaya Negeri Village still faces challenges in fulfilling SDGs indicator number 5, such as the low participation of women in the Village Consultative Body (BPD) and the low Gross Participation Rate (APK) of women in education at the SMA/SMK/MA level. However, this study also found great potential to increase women's involvement through more gender-responsive village regulations and more inclusive empowerment programmes.